2011
DOI: 10.1007/s10641-011-9898-8
|View full text |Cite
|
Sign up to set email alerts
|

Relating the swimming movements of green sturgeon to the movement of water currents

Abstract: Animals swimming in tidal environments continuously interact with water currents which may either hinder or aid their movement. It is difficult to observe the orientation of an organism relative to the current when it is swimming in the wild without specialized telemetry; however, using the total recorded movement vector and the current vector, one can use vector analysis to calculate the actual movement of the animal. Here, we apply this method to six tracks of green sturgeon (Acipenser medirostris) in the Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The apparent tidal modulation of acoustically tagged smolts in the Penobscot Estuary was indicative of selective tidal stream transport (STST; Forward & Tankersley, 2001). STST is a behavioural tactic that reduces energetic costs of migration for marine animals (Forward & Tankersley, 2001), and several examples exist in a number of invertebrate (Queiroga, 1998;Forward et al, 2003;Criales et al, 2011) and fish species (Barbin, 1998;McCleave & Arnold, 1999;Kelly & Kimley, 2012), including adult sockeye salmon Oncorhynchus nerka (Walbaum 1792) (Levy & Cadenhead, 1995). Changes in depth by S. salar smolts in the Penobscot Estuary suggested that fish were located deeper during incoming tides than outgoing tides, a behaviour that would result in increased, rather than decreased exposure to SW during tidal cycles as would be expected from the laboratory results.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent tidal modulation of acoustically tagged smolts in the Penobscot Estuary was indicative of selective tidal stream transport (STST; Forward & Tankersley, 2001). STST is a behavioural tactic that reduces energetic costs of migration for marine animals (Forward & Tankersley, 2001), and several examples exist in a number of invertebrate (Queiroga, 1998;Forward et al, 2003;Criales et al, 2011) and fish species (Barbin, 1998;McCleave & Arnold, 1999;Kelly & Kimley, 2012), including adult sockeye salmon Oncorhynchus nerka (Walbaum 1792) (Levy & Cadenhead, 1995). Changes in depth by S. salar smolts in the Penobscot Estuary suggested that fish were located deeper during incoming tides than outgoing tides, a behaviour that would result in increased, rather than decreased exposure to SW during tidal cycles as would be expected from the laboratory results.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, there has been increasing recognition that external constraints in particular may play a larger role in shaping an organism's movement path than previously considered (Wilson et al 2012;Shepard et al 2013;Brownscombe et al 2017;Gallagher et al 2017). In estuarine habitats, one such external force is the seasonal and daily hydrological variance, which is generated by complex bathymetry and water flux from various inshore and offshore sources (Brodersen et al 2008;Anderson and Beer 2009;Forsythe et al 2012;Kelly and Klimley 2012). Due to the presence and variability of these currents, it is likely that different species that reside in or transit through estuaries will exhibit plasticity in their movement in response to the currents.…”
Section: Introductionmentioning
confidence: 99%
“…Lunar and tidal cycles have long been shown to affect the movements of many fish species and decapod crustaceans (Forward & Tankersley 2001;Reebs 2002;Hare et al 2005;Keefer et al 2013) and generally are co-dependent on one another. Kelly & Klimley (2012) noted Green Sturgeon (Acipenser medirostris) swimming into the current while maintaining position just off the bottom which likely allows them to more efficiently maintain buoyancy while swimming. Thus, it is possible that flow conditions experienced during a rising tide caused Gulf Sturgeon to change their swimming behaviour in a way which made them more susceptible to capture in the anchored gear.…”
Section: Discussionmentioning
confidence: 99%